RAISING CHILDREN THROUGH OUTDOOR GAMES - Tashpulatov , Farkhad Alisherovich (Innovative Development in Educational Activities, 2023)
This article describes raising children using outdoor games. Outdoor games are usually considered as a means of exercising children in walking, running, jumping and other types of movements. The need for movement, the physical activity of a child, physiologically based, has a positive effect on his physical and mental development, improvement of all functional systems of the body.